2019
DOI: 10.3389/fgene.2019.01238
|View full text |Cite
|
Sign up to set email alerts
|

Population Differentiation and Demographic History of the Cycas taiwaniana Complex (Cycadaceae) Endemic to South China as Indicated by DNA Sequences and Microsatellite Markers

Abstract: Historical geology, climatic oscillations, and seed dispersal capabilities are thought to influence the population dynamics and genetics of plants, especially for distribution-restricted and threatened species. Investigating the genetic resources within and among taxa is a prerequisite for conservation management. The Cycas taiwaniana complex consists of six endangered species that are endemic to South China. In this study, we investigated the relationship between phylogeographic history and the genetic struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 105 publications
2
4
0
Order By: Relevance
“…The AMOVA results were consistent with those of other studies, which showed that the genetic differentiations of many Cycas species were distributed among populations based on the cpDNA data (Feng et al, 2014(Feng et al, , 2017Feng, Zheng, & Gong, 2016;Wang et al, 2019;Xiao et al, 2020;Yang et al, 2017;Zheng et al, 2016). Moreover, nuclear genes explored the opposite results (Feng et al, 2014;Feng, Zheng, & Gong, 2016;Wang et al, 2019;Xiao et al, 2020;Yang et al, 2017), genetic variations were mainly distributed within populations with the species C. dolichophylla as an exception, whose genetic variations among populations was greater than that within populations (Zheng et al, 2016). In Cycas, the chloroplast DNAs are maternal inheritance (Zhong et al, 2011), and genetic materials are transmitted by seeds.…”
Section: Low Genetic Diversity and Genetic Differentiationsupporting
confidence: 91%
See 2 more Smart Citations
“…The AMOVA results were consistent with those of other studies, which showed that the genetic differentiations of many Cycas species were distributed among populations based on the cpDNA data (Feng et al, 2014(Feng et al, , 2017Feng, Zheng, & Gong, 2016;Wang et al, 2019;Xiao et al, 2020;Yang et al, 2017;Zheng et al, 2016). Moreover, nuclear genes explored the opposite results (Feng et al, 2014;Feng, Zheng, & Gong, 2016;Wang et al, 2019;Xiao et al, 2020;Yang et al, 2017), genetic variations were mainly distributed within populations with the species C. dolichophylla as an exception, whose genetic variations among populations was greater than that within populations (Zheng et al, 2016). In Cycas, the chloroplast DNAs are maternal inheritance (Zhong et al, 2011), and genetic materials are transmitted by seeds.…”
Section: Low Genetic Diversity and Genetic Differentiationsupporting
confidence: 91%
“…Climate fluctuation during the Quaternary period had effects on the population historical dynamics of Cycas species, and different species had different responses to glacial and interglacial influences (Wang et al, 2019 ). The mismatch distribution analysis of nuclear genes AC 5, PPRC , and AAT showed a unimodal curve, which were consistent with the BSP results, indicating that C. taiwaniana experienced an expansion event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of conservation units (CUs) is important for the conservation and management of threatened species, providing managers and policy‐makers with a clear understanding of the boundaries of population units (Funk et al, 2012; Li, Milne, et al, 2020; Li, Wang, et al, 2020). A comprehensive understanding of population structure, genetic differentiation and demographic history is crucial for an understanding of the evolutionary history of a species, and the implications of these issues for the conservation of the organisms (Wang et al, 2019). Genetic markers such as microsatellite loci, chloroplast DNA and mitochondrial DNA may be inadequate for determining the population genetic structure of species with complex demographic histories.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive understanding of population structure, genetic differentiation and demographic history is crucial for an understanding of the evolutionary history of a species, and the implications of these issues for the conservation of the organisms (Wang et al, 2019). Genetic markers such as microsatellite loci, chloroplast DNA and mitochondrial DNA may be inadequate for determining the population genetic structure of species with complex demographic histories.…”
Section: Introductionmentioning
confidence: 99%